2004
DOI: 10.1097/01.prs.0000142416.91524.4c
|View full text |Cite
|
Sign up to set email alerts
|

Distally Based Anterolateral Thigh Flap: An Anatomic and Clinical Study

Abstract: The distally based anterolateral thigh flap has been used for coverage of soft-tissue defects of the knee and upper third of the leg. This flap is based on the septocutaneous or musculocutaneous perforators derived from the lateral circumflex femoral system. The purpose of this study was to examine the results of anatomical variations of the descending branch of the lateral circumflex femoral artery and the retrograde blood pressure of the descending branch of the lateral circumflex femoral artery so that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 14 publications
4
97
1
7
Order By: Relevance
“…Rarely, the transverse branch can be a direct branch of the LCFA or be missing. Sabancıogullari et al [29], and Pan et al [26] reported the same.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Rarely, the transverse branch can be a direct branch of the LCFA or be missing. Sabancıogullari et al [29], and Pan et al [26] reported the same.…”
Section: Discussionsupporting
confidence: 60%
“…The ascending branch runs under the TFL muscle and anastomosis with the superior gluteal and the deep circumflex iliac arteries and supplies the greater trochanter, the head and the neck of femur [13,15,28,29,31]. Some authors describe that LCFA gives only the ascending and the descending branch, while the transverse one is the branch of the ascending one [17,26]. The TFL flap has a constant vascular supply from the ascending branch of the LCFA with its accompanying commitant veins, and enters the muscle on its deep surface, from 6 cm to 8 cm below the iliac crest at the level of the greater trochanter.…”
Section: Introductionmentioning
confidence: 99%
“…The antero-lateral thigh flap is based on the perforators from the descending branch of the lateral circumflex femoral artery, which are clustered within a 3 cm radius of the midpoint of a line which joins the anterior superior iliac spine and the superolateral patella. The descending branch anastomoses with the superior lateral genicular artery, which allows a distallybased flap to be harvested, with the pivot point 3-10 cm above the knee joint [25]. The anteromedial thigh flap is based on a major perforator from the rectus femoris branch of the descending branch of the lateral circumflex femoral artery, which is present in 51% individuals.…”
Section: Discussionmentioning
confidence: 99%
“…También se ha descrito el adelgazamiento del colgajo hasta el extremo de convertirlo en un colgajo meramente cutáneo irrigado por el plexo subdérmico. Presenta la dificultad de la disección microquirúrgica del vaso perforante hasta el plexo subdérmico y se ha utilizado para la cobertura del dorso del pie con la ventaja de obtener un buen resultado cosmético sin la necesidad de desgrasarlo en un segundo tiempo (23).…”
Section: Reconstruccion De Extremidadesunclassified